Financial deepening in economic development - Shaw, Edward S. (New York: Oxford University Press, 1973)
This is an old-fashioned book. It is neoclassical in insisting that relative price counts in economic development. It is monetarist in insisting that money and its relative prices affect real aspects of the development process. It draws attention to financial markets for the role that they can play in making growth paths steeper for relatively poor economies and more stable.
Includes index
Includes bibliographical references.
usc 21/9/17
Loans
Keywords: Finance; Developing countries